2012
DOI: 10.1111/j.1471-1842.2012.00990.x
|View full text |Cite
|
Sign up to set email alerts
|

Making evidence‐based decisions when organising information retrieval training for nurses and head nurses

Abstract: Using the PICO (Problem, Intervention, Comparison, Outcome) 1 framework, this feature presents a case study on the information skills strand of a continuing education programme delivered at Kuopio University Hospital in Finland for nurses and head nurses.H.S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…This is surprising since everyone on the course had the opportunity to learn about searching for research knowledge, though it is only a one part of the use of research. The librarians were involved in the training as educators and their role was highly appreciated [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is surprising since everyone on the course had the opportunity to learn about searching for research knowledge, though it is only a one part of the use of research. The librarians were involved in the training as educators and their role was highly appreciated [26].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was training in information retrieval by a librarian (Ovaska 2012). This course gave students information literacy skills training, necessary for the successful implementation of EBP and EBL and also for continuing professional development.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…found that nurse/librarian collaborations not only increase nurses' knowledge of EBP, but also effectively eliminate barriers to EBP access . These partnerships have been used effectively in past efforts in nursing education and in CE opportunities for licensed staff nurses working in the hospital …”
Section: Introductionmentioning
confidence: 99%
“…17,22 These partnerships have been used effectively in past efforts in nursing education [23][24][25][26] and in CE opportunities for licensed staff nurses working in the hospital. 17,20,[27][28][29] Discussion of outreach to PHNs has been limited within the literature. In 1994, Self et al…”
Section: Introductionmentioning
confidence: 99%